Operative and Functional Outcome After Pulmonary Endarterectomy for Advanced Thromboembolic Pulmonary Hypertension. Issue 1 (4th November 2015) - Leung Wai Sang, Stephane; Morin, Jean‐Francois; Hirsch, Andrew
Abstract: Aim: To evaluate the midterm hemodynamic and functional outcome of pulmonary endarterectomy (PEA) for patients with advanced chronic thromboembolic pulmonary hypertension (CTEPH). Methods: Thirty‐eight consecutive patients underwent PEA for CTEPH from May 2004 to March 2012. All patients were followed prospectively at six months postoperatively and annually thereafter. Each patient underwent serial cardiopulmonary exercise testing (CPET) and transthoracic echocardiography, and were followed for up to four years. Results: Overall, 31.5% (12/38) of patients had Jamieson class II disease while 65.8% (25/38) had class III disease. There were three in‐hospital mortalities (7.9%), all of which had baseline pulmonary vasculature resistance (PVR) greater than 1400 dynes‐sec‐cm −5 . Preoperative PVR and mean pulmonary artery pressure were 1209 ± 723 dynes‐sec‐cm −5 and 50 ± 14 mmHg, respectively, signifying a high‐risk operative group. Ninety‐seven percent of patients were in NYHA class III or IV preoperatively. At median follow‐up of 29 months 89.5% (17/19) of patients were in NYHA class I or II. CPET revealed a progressive increase in peak oxygen consumption from 16.5 ± 4.1 ml/kg/min at first follow‐up, to a plateau of 20.2 ± 5.6 ml/kg/min (p = 0.032) at two years. Conclusions: CPET can be used to quantify progress in functional capacity post‐CTEPH, although improvements in peak oxygen consumption plateau at two years. doi: 10.1111/jocs.12646 (J Card Surg 2016;31:3–8)